Ethical research on the implementation of DRGs in Switzerland – a challenging project (Swiss Medical Weekly, 2012)
Diagnosis Related Groups (DRGs) are currently being introduced on a national scale as a prospective reimbursement scheme in Swiss in-patient hospital care, replacing any remaining retrospective day-rate arrangements. DRGs are expected to promote transparency and efficiency while helping to contain health care costs. The governmental decision to introduce DRGs has caused considerable controversy among different stakeholders, due to diverging appraisals of what will happen when DRGs are introduced as an economic management tool in Switzerland. The controversial discourse on DRGs is particularly interesting from an ethical point of view, since all arguments inevitably contain ethical considerations. In this paper we summarise the results of our exploratory ethical studies that have led to a larger research project funded by the Swiss National Science Foundation: “Impact of Diagnosis-Related Groups (DRGs) on patient care and professional practice” (IDoC). In section 1: ‘Developing an understanding of the ethical issues at stake’ we briefly explain how DRGs work, what the intended effects are, what the public is concerned about and what the scientific research tells us so far. In section 2: ‘Developing an ethical framework for research on DRGs in Switzerland’ we summarise the ethical issues and explain the ethical framework we will use in order to perform research on the complex issue of DRGs in Switzerland. Only once a profound understanding of the challenges exists can research on the ethical implications of DRGs be successful.